Application of the Fair Use Principle to Songs Modified on Digital Platforms Based on Positive Law in Indonesia - Elsha Yoleda; Rika Ratna Permata; Tasya Safiranita Ramli (Widya Yuridika, 2023)
The song entitled "Masker dan Vaksin" released by Satuan Tugas Penanganan COVID-19 on YouTube is a modified song from the song "Galih dan Ratna" by Guruh Sukarno Putra. In addition, Indomusikgram creates video content on TikTok entitled "Tips Jaga Kesehatan" by modifying the song "Ampar-ampar Pisang" which was created by Hamiedan AC. The song contains a message to the public about preventing the COVID-19 virus. This research will focus on legal protection for the creators of modified song in digital platforms based on Law No. 28/2014 concerning Copyright. Furthermore, this research was also conducted to determine whether the fair use principle can be applied in modifying songwriting works on digital platforms based on Law Number 19/2016 concerning Information and Electronic Transactions. The writing method used is a normative juridical approach. This writing uses descriptive analytical writing specifications. In this writing phase is also done by writing literature by reffering to the laws and regulations, literature and other relevant documents. The results of this research shows that songwriters have the right to include their names in uploaded content on YouTube and TikTok by Indomusicgram and Satuan Tugas Penanganan COVID-19 based on Article 44 of Law No. 28/2014 concerning Copyright. Creators also have the right to refuse if they object to the modification of the song that occurs. Furthermore, the ITE Law does not regulate the principle of fair use of copyright. So it can be concluded from Article 25 of the ITE Law, the application of the principle of fair use to song copyrighted works modified on digital platforms during the COVID-19 pandemic still refers to the Copyright Law.